Young boy falls prey to gecko – A rare case of animal bite - Yap, Pauline; Saw, Joo Ee; Wan Sulaiman, Wan Azman (Kerman University of Medical Sciences, 2024)
According to reports from the United States, Australia, and Italy, animal bites in the human population are predominantly dog (80%) and cat (< 20%) bites [1]. The rest are caused by a very small percentage of wildlife, farm animals, rodents, and other pets. There are few epidemiological studies on lizards in Malaysia. Available data shows 106 lizard species in Peninsular Malaysia, excluding the Bornean species (ADD on REF-1.grismer,2-lizard of Borneo). Lizards are a rare cause of animal bites in humans, especially in pediatric populations. There are over 3000 species of lizards with varying sizes, ranging from small house lizards to medium-sized geckos and larger monitor lizards with crocodile appearance. The world's largest lizard, the Komodo dragon, is claimed to kill by envenomation rather than exerting brute force[2]. Despite this wild claim, only two lizards are venomous and medically significant: the Gila monster (Heloderma suspectum) from the southwest United States and Mexico and the Mexican beaded lizard (Heloderma horridum)[2]. Significant morbidity has been reported from their bites. Reported fatal complications from lizard bites include severe kidney injury and compartment syndrome (add ref 1, Arvind, 2, SAnjay). Many cases have reported bites from larger-sized lizards, but to the best of our knowledge, none in the literature reports bites from relatively smaller-sized geckos. However, the incidence of lizard bites have increased because the current generation has started a new trend of keeping lizards as pets (ref. Wong et al.). This case report intends to create awareness of the potential threats of relatively smaller lizards to humans, especially in the pediatric population.